Residual excessive sleepiness in patients with obstructive sleep apnea on treatment with continuous positive airway pressure. Issue 6 (November 2016) - Dongol, Eptehal M.; Williams, Adrian J.
Abstract : Purpose of review: One of the most common causes of excessive daytime sleepiness in clinical practice is obstructive sleep apnea syndrome (OSAS). So far, continuous positive airway pressure (CPAP) is the most effective treatment for OSA. Some of the patients do not improve on CPAP and remain sleepy despite using CPAP. This review provides updated information about the possible causes of residual sleepiness whilst using the CPAP in patients with OSAS. Recent findings: Prevalence of OSAS has increased recently to 23.4% in women and 49.7% in men. Periodic limb movement, behaviorally induced insufficient sleep syndrome and depression are the most common causes of persistent sleepiness on CPAP. Residual sleepiness after exclusion of all possible causes is 6%. Summary: There is still lack of sufficient evidence about the accurate characteristics and possible causes of this residual sleepiness and how to address this in large prospective studies.